Novel full reference perceptual quality metric for audio-visual asynchrony - Yao-du WEI; Xiang XIE; Jing-ming KUANG; Xin-lu HAN (Tongxin xuebao)
A full reference model was proposed to evaluate the perceptual quality of audiovisual asynchrony.A standard synchronization process was used to determine the time difference between audio and video.The mapping between the time difference and the perceptual quality was derived by co-inertia analysis.The co-inertia analysis extracted the most related component from audio and video features,and then formed a mapping for each audiovisual sequence.Audiovisual contents were divided into three categories:clean speech,non speech and mixed speech.The clean speech category was further split into two subcategories.Audio and video features were chosen separately for each category.Subjective test results showed that the proposed model conforms well with subjective results.